4P ANALYSIS BASED ON GREEN MARKETING ON PURCHASE DECISION IN PRODUCT THE BODY SHOP WITH BRAND IMAGE AS VARIABLE MEDIATION - Putri Maya Sulistiani; Lenny Christina Nawangsari; Kusumo Bintoro (Jurnal Scientia, 2023)
This research is motivated by many companies engaged in the beauty industry, both local and foreign companies. With the continued development of the beauty industry, people have many choices to choose the desired beauty products. With the development of the beauty industry in Indonesia, companies must be able to implement strategies so that their products remain the people's choice. One of the strategies needed is a marketing strategy. The issue of global warming which is currently getting attention from the public, makes people become more careful in choosing a product because they are trying to reduce the effects of global warming. Therefore, currently the beauty industry is starting to carry out a green marketing strategy in marketing their products by using materials that do not damage the environment. One of the beauty companies that uses a green marketing strategy is The Body Shop. The purpose of this study was to determine the effect of green marketing 4P on purchase decisions, either directly or mediated by the brand image variable. The type of research used is quantitative research. The data presented in this study were obtained through questionnaires distributed to 183 respondents. Statistical analysis using the PLS SEM method for model and hypothesis testing. The results of this study indicate that green marketing has a direct effect on brand image and green marketing has an effect on purchase decisions, and brand image has a direct effect on purchase decisions, and green marketing has an effect on purchase decisions mediated by brand image.